Efficient photorecovery of noble metals from solution using a γ-SiW10O36/surfactant hybrid photocatalyst - Kida, Tetsuya (Langmuir : the ACS journal of surfaces and colloids, 2013)
In recent years, the recovery of noble metals from waste has become very important because of their scarcity and increasing consumption. In this study, we attempt the photochemical recovery of noble metals from solutions using inorganic-organic hybrid photocatalysts. These catalysts are based on polyoxometalates such as PMo(12)O(40)(3-), SiW(12)O(40)(4-), and γ-SiW(10)O(36)(8-) coupled with a cationic surfactant, dimethyldioctadecylammonium (DODA). The three different photocatalysts dissolved in chloroform were successful in photoreducing gold ions dissolved in water in a two-phase (chloroform/water) system under UV irradiation (λ < 475 nm). The γ-SiW(10)O(36)/DODA photocatalyst exhibited the best activity and recovered gold from solution efficiently. It was suggested that one-electron reduced γ-SiW(10)O(36)(9-) formed by the UV irradiation reduced gold ions. As a result, large two-dimensional particles (gold nanosheets) were produced using the γ-SiW(10)O(36)/DODA photocatalyst, indicating that the reduction of gold ions occurred at the interface between chloroform and water. The γ-SiW(10)O(36)/DODA photocatalyst was able to recover metals such as platinum, silver, palladium, and copper from deaerated solutions. The selective recovery of gold is possible by controlling pH and oxygen concentration in the reaction system